Bargaining power, structural change, and the falling U.S. labor share - Michael Cauvel; Aaron Pacitti (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
One of the most significant stylized facts in the U.S. economy since the 1970s has been the decline in the share of national income accruing to labor. Many recent studies have sought to explain this trend, with most explanations focusing on structural changes such as deindustrialization, globalization, financialization, rising market concentration, and technological change. We argue that all of these forces primarily operate through a bargaining power channel measured by the cost of job loss, and that the reduction in labor's share of income has been driven by lower bargaining power for workers. Moreover, we contend that business cycle fluctuations in the cost of job loss can help to explain the short-run behavior of the labor share as well. We examine these hypotheses for the United States from 1960-2016. We first estimate the relationship between the cost of job loss and labor's share of income using a bounds-testing approach and find significant negative relationships for both the short and long run. However, the short-run effects are sensitive to the inclusion of policy-related control variables. We then create an index of structural change and estimate regressions of the cost of job loss, finding that increases in this index have both increased the cost of job loss and amplified its volatility over the course of the business cycle. Our empirical analysis therefore supports the hypothesis that the decline in the labor share is driven by decreased labor bargaining power and suggests that structural economic changes and weak economic performance in the U.S. have increased inequality.
Keywords: E25; E24; E12; 330; labor share; bargaining power; cost of job loss; structural change